Ubuntu translanguaging: An alternative framework for complex multilingual encounters. Issue 3 (30th September 2016) - Makalela, Leketi
Abstract: Multilingual education practices worldwide are still characterised by monolingual bias that can be tracked as far back as the European Enlightenment period. Yet the majority of learners employ meta-discursive regimes that are versatile, mobile and fluid in response to transnational mobility and blurring of boundaries between nation states in the 21st century. Taking account of African sociolinguistic contexts predating European colonialism, I draw attention to the obsolete nature of one-ness ideology and its sequential, linear and positivist methods in African classrooms. I argue for the African value system of ubuntu as a heuristic to theorise infinite relations of dependency between languages and literacies and how this system reflects a cultural competence upon which literacy practices need to be anchored. Useful pedagogic recommendations for teaching literacy from the ubuntu perspective are provided for adaptation in related contexts.